2019
DOI: 10.1186/s12876-019-1144-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of over-the-scope-clip system for the treatment of acute upper non-variceal gastrointestinal bleeding: a systematic review and meta-analysis

Abstract: BackgroundConventional endoscopic treatments can’t control bleeding in as many as 20% of patients with non-variceal gastrointestinal (GI) bleeding. Recent studies have shown that over-the-scope-clip (OTSC) system allowed for effective hemostasis for refractory GI bleeding lesions. So we aimed to conduct a systematic review to evaluate the effectiveness and safety of the OTSC system for management of acute non-variceal upper GI bleeding.MethodA comprehensive literature search was conducted on PubMed, EMBASE, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Separately, in a meta-analysis by Zhong et al evaluating 16 studies and 769 patients with non-variceal bleeding, OTSC was successfully placed in 95.7% of lesions, and 84.2% had no re-bleeding. Twelve of the studies identified a mortality rate of 10.9% (3.9% related to bleeding) [ 6 ].…”
Section: Clinical Applications Of Otscmentioning
confidence: 99%
“…Separately, in a meta-analysis by Zhong et al evaluating 16 studies and 769 patients with non-variceal bleeding, OTSC was successfully placed in 95.7% of lesions, and 84.2% had no re-bleeding. Twelve of the studies identified a mortality rate of 10.9% (3.9% related to bleeding) [ 6 ].…”
Section: Clinical Applications Of Otscmentioning
confidence: 99%
“…In a systematic review of OTSCs, successful hemostasis was achieved in 84% of 761 lesions, including 75% of lesions due to peptic ulcer disease. 34 Some have argued that OTSCs may be preferred as first-line therapy over epinephrine with TTS clips for hemostasis in bleeding from high-risk peptic ulcers (ie, those with visualized arterial bleeding or a visible vessel) given observed decreases in rebleeding events. 35 Despite the advantages of OTSCs, endoscopists should be mindful of the potential complications of OTSC use, including luminal obstruction, particularly in the duodenum, and perforation, which occurs in 0.3% to 2% of cases.…”
Section: Failure Of Endoscopic Therapy To Control Peptic Ulcer Bleedingmentioning
confidence: 99%
“…Careful decision-making with consideration of the location, size, and depth of lesions is required when deciding on OTSC placement. 34,36 A newer endoscopic tool developed for refractory bleeding from peptic ulcers and other causes is hemostatic powder. Hemostatic powders accelerate the coagulation cascade, leading to shortened coagulation times and enhanced clot formation.…”
Section: Failure Of Endoscopic Therapy To Control Peptic Ulcer Bleedingmentioning
confidence: 99%
“…With the advancement of endoscopic techniques, many gastrointestinal lesions have been properly managed, but there are still challenges. Most upper non-variceal gastrointestinal bleeding (UNVGIB) could be treated by conventional endoscopic therapies, but recent studies have shown that some UNVGIB such as Dieulafoy's lesion and refractory bleeding could not be treated successfully and develop recurrence easily after standard endoscopic therapies such as epinephrine injections, hemoclips, or coagulation ( 1 , 2 ). Equally, although many treatments have been attempted for the closure of perforations and fistulas, more and more iatrogenic gastric perforations are raised during endoscopic resection such as endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD), which could be handled by endoscopic closure and conservative management.…”
Section: Introductionmentioning
confidence: 99%